Burnout among healthcare providers in the complex environment of the Middle East: a systematic review - Z. Chemali; F. L. Ezzeddine; B. Gelaye; M. L. Dossett; J. Salameh; M. Bizri; B. Dubale; G. Fricchione (BMC, 2019)
Abstract Background Burnout is a syndrome characterized by emotional exhaustion, increased depersonalization, and a diminished sense of personal accomplishment due to chronic emotional stress at work. Burnout impacts job satisfaction, job performance, vulnerability to illnesses, and interpersonal relationships. There is a gap in the systematic data on the burden of burnout among healthcare professionals from different sectors of healthcare in Middle Eastern countries. Our objective was to examine the burden of burnout among healthcare providers in the Middle East, how it was assessed, which sectors were included, and what interventions have been used. Methods Articles were found through a systematic review of search results including PubMed, Web of Science (Thomson Reuters), and PsycINFO (EBSCO) using search terms reflecting burnout in Middle Eastern countries among populations of healthcare providers. Studies were included if they examined a quantitative measure of burnout among healthcare providers in the Middle East. Results There were 138 articles that met our inclusion criteria for this systematic review. Studies focused on burnout in the Middle East among physicians (N = 54 articles), nurses (N = 55), combined populations of healthcare workers (N = 22), and medical students (N = 7). The Maslach Burnout Inventory was the most common tool to measure burnout. Burnout is common among physicians, nurses, and other healthcare professionals, with prevalence estimates predominantly ranging between 40 and 60%. Burnout among healthcare providers in the Middle East is associated with characteristics of their work environments, exposure to violence and terror, and emotional distress and low social support. Conclusions Burnout is highly prevalent among healthcare providers across countries in the Middle East. Previous studies examining burnout in this region have limitations in their methodology. More thoroughly developed epidemiologic studies of burnout are necessary. Health system strengthening is needed in a region that has endured years of ongoing conflict, and there is an urgency to design and implement programs that tackle burnout among health professionals.